Science in stories: Implications for Latine children’s science learning through home-based language practices - Haden, Catherine A.; Melzi, Gigliana; Callanan, Maureen A. (Frontiers in Psychology, 2023)
There is growing interest in stories as potentially powerful tools for science learning. In this mini-review article, we discuss theory and evidence indicating that, especially for young children, listening to and sharing stories with adult caregivers at home can make scientific ideas and inquiry practices meaningful and accessible. We review recent research offering evidence that stories presented in books can advance children's science learning. Nonetheless, most of this work focuses on middle-class European-American U. S. children and involves narrative story books. Given the national imperative to increase Latine representation in STEM education and career pursuits in the U. S., we argue that it is vital that we broaden the definition of stories to include oral narrative storytelling and other conversational routines that Latine families engage in at home. Cultural communities with firmly rooted oral traditions, such as those from Latin American heritage, rely frequently on oral storytelling rather than book reading to convey world and community knowledge to young children. Therefore, we advocate for a strengths-based approach that considers Latine families’ everyday practices around science and storytelling on their own terms instead of contrasting them with European-American middle-class practices. We offer support for the view that for young children in Latine communities, culturally relevant oral practices, including personal narrative storytelling, can engender significant opportunities for family science learning at home.